Pacification in Algeria, 1956-1958 - Galula, David, 1919-1967 (MG (Rand Corporation), 2006)
When Algerian nationalists launched a rebellion against French rule in November 1954, France, mired in similar wars for independence in its colonial territories, was in a poor position to cope with further upheaval. The Algerian strategy encompassed varying approaches and was more adaptable than that of the French, necessitating a rethinking of traditional counterinsurgency methods. In this volume, originally published in 1963, David Galula reconstructs the story of his highly successful command in the district of Greater Kabylia, east of Algiers, at the height of the rebellion, and presents his theories on counterinsurgency and pacification. In the process, he confronts the larger political, psychological, and military aspects of the Algerian war, and provides a context for present-day counterinsurgency operations. This groundbreaking work, featuring a new foreword by Bruce Hoffman, retains its relevancy as a challenge to traditional counterinsurgency tactics and presents approaches to predicting, managing, and resolving insurgent and guerilla conflict. The parallels between the Algerian war and modern warfare are striking, and lessons can be extracted from French successes and failures in its drive to contain and manage the Algerian uprising.